2015
DOI: 10.1902/jop.2014.140025c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Human Chorion Membrane Allograft for Recession Coverage: A Case Series

Abstract: Background: Membranes of human placentas have been used in the field of medicine for skin grafts, treatment of burns, and ulcerated skin conditions with great success. The use of placenta allografts in dentistry is a more recent development, with the first commercial product being made available in 2008. The unique inherent biologic properties in placenta allografts enhance wound healing and may propagate regeneration.Methods: Ten healthy adult patients presenting with 21 Miller Class I gingival recession (GR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
2
26
0
1
Order By: Relevance
“…This was in accordance Esteves et al. 's study, where there was reduction of HGR from 3.14 ± 1.24 to 2.76 ± 1.00 when placental membranes were used for the treatment of recession defects. The significant reduction in HGR could be due to the presence of growth factors in placental membranes that aid in the formation of granulation tissue by stimulating fibroblast growth and neovascularization, as seen in Koizumi et al.…”
Section: Discussionsupporting
confidence: 92%
“…This was in accordance Esteves et al. 's study, where there was reduction of HGR from 3.14 ± 1.24 to 2.76 ± 1.00 when placental membranes were used for the treatment of recession defects. The significant reduction in HGR could be due to the presence of growth factors in placental membranes that aid in the formation of granulation tissue by stimulating fibroblast growth and neovascularization, as seen in Koizumi et al.…”
Section: Discussionsupporting
confidence: 92%
“…Gingival index (GI)[12]GR depth (GRD) calculated from the cementoenamel junction (CEJ) to the free gingival margin at the center of facial surface[913]GR width (GRW) calculated across the labial surface and at CEJ[913]Relative attachment level (RAL) measured midlabially with the reference point situated at the buccal cusp/incisal edge[91314]Complete or partial root coverage[91314] estimated using the following formula:Width of keratinized tissue (KTW) measured from the gingival margin to the mucogingival junction (MGJ), at the mid-buccal point. The MGJ was noted by means of Schiller's iodine.…”
Section: Methodsmentioning
confidence: 99%
“…At 6 months, the authors reported mean root NSD no significant difference, SCTG subepithelial connective tissue graft, Pts/Def-T patient/defect numbers in the test group, Pts/Def-C patient/defect numbers in the control group, mean RC-T mean root coverage in the test group, mean RC-C mean root coverage in the control group, CPF coronally positioned flap, ADM acellular dermal matrix allograft (AlloDerm®), CM porcine collagen matrix (Mucograft®), EMD enamel matrix derivative (Emdogain®), LPRF leukocyte-and platelet-rich fibrin, rhPDGF-BB recombinant human platelet-derived growth factor BB, β-TCP β-tricalcium phosphate, AFCC autologous fibroblast cell culture, UC-MSC umbilical cord-mesenchymal stem cell, LLLT low-level laser therapy coverage of 87%, along with increased gingival thickness and width of keratinized tissue. Human chorion membrane was tested on isolated/multiple gingival recession defects (21 defects in 10 subjects) in a case series report [55]. The mean root coverage was 90% at 6 months, and all sites with an originally thin biotype were converted to a thick biotype.…”
Section: Other Biomaterials and Proceduresmentioning
confidence: 99%